Irwin Edman papers - Edman, Irwin, 1896-1954.; Edman, Irwin, 1896-1954.; Edman, Irwin, 1896-1954.; Edman, Irwin, 1896-1954.
Correspondence, drafts and copies of books, articles, book reviews, speeches and lectures, poems, unidentified copies and fragments, and clippings concerning the period of Edman's career as instructor and professor of philosophy at Columbia University, and as special lecturer at other colleges and universities. Among the drafts and copies are those for his books, The Philosophy of Santayana (1936), Candle in the Dark (1939), and Under Whatever Sky (1951).
Philosopher, educator, and author.
Collection material in English.
Keywords: Columbia University -- Faculty; Philosophy; Authors; Educators; Philosophers